CYTOTAXONOMIC STUDIES OF SOME IRANIAN VICIA SPECIES (FABACAEA) (Journal of Sciences, Islamic Republic of Iran)
This study concerns the cytotaxonomic investigations on twelve species belonging to three sections from the genus Vicia in Iran. A taxonomic background of the genus is given in brief. The previous counts reported for the genus in Index to plant chromosome number are summarized. In addition to one new count, the chromosome numbers of four species are reported for the first time. Briefly, the results of this study are discussed and compared with the reported counts